2022
DOI: 10.1038/s41419-022-04969-5
|View full text |Cite
|
Sign up to set email alerts
|

Function of PHEX mutations p.Glu145* and p.Trp749Arg in families with X-linked hypophosphatemic rickets by the negative regulation mechanism on FGF23 promoter transcription

Abstract: X-linked hypophosphatemic rickets (XLH) is characterized by increased circulating fibroblast growth factor 23 (FGF23) concentration caused by PHEX (NM_000444.5) mutations. Renal tubular resorption of phosphate is impaired, resulting in rickets and impaired bone mineralization. By phenotypic-genetic linkage analysis, two PHEX pathogenic mutations were found in two XLH families: c.433 G > T, p.Glu145* in exon 4 and c.2245 T > C, p.Trp749Arg in exon 22. Immunofluorescence showed that the localization of p.G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It is predominantly expressed in osteoblasts, osteocytes, cartilage, and odontoblasts, and in these cells, PHEX deficiencies impair the cellular trafficking, endopeptidase activity, and FGF23 signaling that, in turn, reduce renal phosphate reabsorption, resulting in abnormal bone mineralization and hypophosphatemia [7]. The regulatory mechanism between PHEX and FGF23 remains unclear, but a recent study demonstrated that PHEX is a direct transcriptional inhibitor of the FGF23 gene [28].…”
Section: Discussionmentioning
confidence: 99%
“…It is predominantly expressed in osteoblasts, osteocytes, cartilage, and odontoblasts, and in these cells, PHEX deficiencies impair the cellular trafficking, endopeptidase activity, and FGF23 signaling that, in turn, reduce renal phosphate reabsorption, resulting in abnormal bone mineralization and hypophosphatemia [7]. The regulatory mechanism between PHEX and FGF23 remains unclear, but a recent study demonstrated that PHEX is a direct transcriptional inhibitor of the FGF23 gene [28].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PHEX may mediate hypophosphatemia by regulating the FGF23 promoter to regulate FGF23 concentration. Therefore, PHEX is a direct transcriptional inhibitor of FGF23 and affects the expression of FGF23 (Gan et al, 2022). Excess and deficiency of FGF23 lead to hypophosphatemia and hyperphosphatemia (see part 4.5), respectively (Fukumoto, 2016).…”
Section: Fgf23 and Related Adhrmentioning
confidence: 99%
“…The PHEX gene contains 22 exons that code for a protein of 749 amino acids, with more than 400 mutations having been recorded so far ( 2 January 2023). However, the mechanism by which these mutations increase FGF23 levels has not been fully elucidated, with preliminary evidence that PHEX is a direct transcriptional inhibitor of FGF23 and is involved in its expression [ 39 ]. There are sporadic cases (between 30 and 54%, depending on the series), in which the PHEX gene mutation frequency is lower than in familial cases.…”
Section: Etiology Of Osteomalaciamentioning
confidence: 99%